The effect of a mental training program on relaxation skills and mental imagery on aggressive behavior associated with competition in handball - merniz, amna (sports creativity, 2025)
The study aimed to highlight the importance and role of relaxation and mental imagery skills in psychological preparation for sports. It sought to answer the following questions: Does training in psychological skills (mental imagery and relaxation) have a positive effect on aggressive behavior among handball players during competitions? Sub-questions: Are there statistically significant differences between the pre- and post-test results of the control group? Are there statistically significant differences between the pre- and post-test results of the experimental group? Are there statistically significant differences between the post-test results of the control and experimental groups in terms of aggressive behavior? What is the opinion of the experimental sample members about the training program based on relaxation and mental visualization in reducing aggressive behavior? The study was conducted on a sample of 14 players, and the original population was comprehensively surveyed using the experimental method for both groups (control and experimental) based on the sports aggression scale and a questionnaire directed at the players as two tools for the study. After collecting, tabulating, analyzing, and discussing the results, the following conclusions were reached - Regular, standardized training in relaxation and mental imagery skills is considered one of the general rules of psychological preparation, as it helps handball players to remain calm and develop concentration, attention, and self-confidence. - Training in relaxation and mental visualization skills helps handball players control their emotions, cope with anxiety appropriate to the level of competition, and manage aggressive behavior during competition.